2008
DOI: 10.1075/eurosla.8.09ive
|View full text |Cite
|
Sign up to set email alerts
|

Interface vulnerability and knowledge of the subjunctive/indicative distinction with negated epistemic predicates in L2 Spanish

Abstract: Much recent research in SLA is guided by the hypothesis of L2 interface vulnerability (see Sorace 2005). This study contributes to this general project by examining the acquisition of two classes of subjunctive complement clauses in L2 Spanish: subjunctive complements of volitional predicates (purely syntactic) and subjunctive vs. indicative complements with negated epistemic matrix predicates, where the mood distinction is discourse dependent (thus involving the syntax-discourse interface). We provide an anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
57
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(66 citation statements)
references
References 40 publications
8
57
0
1
Order By: Relevance
“…The acquisition of Ø topic provides further evidence to the claim that some aspects at the syntax-discourse external interface are acquirable (Ivanov 2012;Iverson et al 2008;Kraš 2008;Rothman 2007Rothman , 2009Slabakova et al 2012;Slabakova and Ivanov 2011;Zhao 2008Zhao , 2012a. The current study supports the proposals of White (2011) andYuan (2010) that interface vulnerability may not be domain-wide in that Ø topic at the syntax-discourse interface is acquired in comparison with some syntax-discourse properties that have proved to be vulnerable to ultimate fossilisation as discussed in Sorace and Filiaci (2006), among others.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…The acquisition of Ø topic provides further evidence to the claim that some aspects at the syntax-discourse external interface are acquirable (Ivanov 2012;Iverson et al 2008;Kraš 2008;Rothman 2007Rothman , 2009Slabakova et al 2012;Slabakova and Ivanov 2011;Zhao 2008Zhao , 2012a. The current study supports the proposals of White (2011) andYuan (2010) that interface vulnerability may not be domain-wide in that Ø topic at the syntax-discourse interface is acquired in comparison with some syntax-discourse properties that have proved to be vulnerable to ultimate fossilisation as discussed in Sorace and Filiaci (2006), among others.…”
Section: Discussionsupporting
confidence: 81%
“…These findings are not fully consistent with the predictions of the IH, but this study is not the only one that has produced findings inconsistent with the IH. The non-acquisition of narrow syntactic properties is also found in Coppieter (1987), Sorace (1993) and Kraš (2011), while the acquirability of the syntax-discourse interface categories are consistent with Ivanov (2012), Iverson et al (2008), Kraš (2008), Rothman (2007), Slabakova et al (2012, Slabakova and Ivanov (2011) and Zhao (2008Zhao ( , 2012a. This study provides supporting evidence to the claim that the (non-)acquirability of a particular interface cannot be generalised (White 2011;Yuan 2010).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Furthermore, Sorace proposed the Interfaces Hypothesis to account for optionality-the alternation of targetlike and non-target-like forms and interpretations in production and comprehension-in both near-native L2 grammars and adult L1 attrition. Other researchers believe that the Interfaces Hypothesis should also be extended beyond optionality to include other non-native patterns (Iverson et al, 2008;Slabakova and Ivanov, this issue).…”
mentioning
confidence: 99%
“…Subsequent research has documented similar asymmetries with respect to other linguistic phenomena (Belletti & Leonini, 2004;Lozano, 2006;Valenzuela, 2006). However, other empirical studies have either failed to detect any apparent signs of instability in domains predicted by the Interface Hypothesis to be vulnerable or suggested that such interface-related difficulties are not pervasive (Donaldson, 2011(Donaldson, , 2012Ivanov, 2012;Iverson, Kempchinsky, & Rothman, 2008;Leal Méndez, Rothman, & Slabakova, in press;Slabakova & Ivanov, 2011;Slabakova, Kempchinsky, & Rothman, 2012). Researchers have also challenged some aspects of the hypothesis on theoretical grounds, including the imprecise formulation of the proposal, difficulty of distinguishing interface-related phenomena from noninterface-related phenomena (and, by the same token, external interfaces from internal interfaces), difficulty of positioning the hypothesis within specific theoretical models of language architecture, and potentially an overly "restrictive" focus of the proposal, originally formulated only for some bilingual populations and not others (Domínguez, 2013;Montrul, 2011;Rothman, 2009;Rothman & Slabakova, 2011;White, 2011).…”
Section: Interfaces: the Integration Problemmentioning
confidence: 95%